Socioeconomic impact of BRAC Schools - Hossain, Altaf; Nath, Samir R; Choudhury, AMR (Research and Evaluation Division, Brac, 2019)
BRAC, one of the largest NGOs in Bangladesh, stru1ed the Non-formal Primary Education (NFPE) programme to help achieve its twin objectives of poverty alleviation and empowerment of the poor. BRAC firmly believes that the raising of the education standard is one of the most effective ways to improve the country's human development records. Many children are deprived of education because of poverty and gender. BRAC developed NFPE programme for those children who had no access to schooling or for those who dropped out. It was expected that NFPE will help them participate effectively in their own socio-economic development by increasing their literacy, numeracy and required life skills. The NFPE programme was started in 1985 with 22 non-formal schools for children aged 8-10 and 11-16 years and by the end of 1999, the total number of schools reached 34,000 and children graduating over 1.5 million. This clearly shows the success of the programme. Recent studies have observed that children of BRAC schools perform better than their counterparts in formal schools in attaining basic education in general and life skills knowledge and writing in particular. However, a very limited attempt has been made to explore the socio-economic effects of NFPE. Therefore it was important to assess the extent to which NFPE contributes to such changes in the desired direction.